Reply to Hellmut Eggers' Comments on "An Association to Improve Evaluation of Development Aid" - Paul Clements (The Evaluation Center at Western Michigan University, 2008)
I would like to thank Hellmut Eggers for his thoughtful comments on my paper. I hope we can collaborate on the project we both hold dear, improving evaluation of development aid! I am particularly grateful for the opportunity to reply to his comments.